Avaliação ultrassonográfica do bulbo ocular em cães submetidos à facoemulsificação com ou sem implante de lente intraocular - Pavan, P. t. [UNESP] (2014)
This study aimed to describe and compare the ultrasonographic alterations in dogs' eyes submitted to facectomy with or without intraocular lens implant (IOL), to assist in the diagnosis of possible alterations related to the surgical procedure and IOL implantation. Nineteen dogs with cataract (21 eyes) were submitted to phacoemulsification and late postoperative evaluation (at five years). The animals were initially submitted to complete ophthalmological exams which preceded the sonogram. Dogs were divided in three groups: (CA) aphakic dogs (n= 11); (PP) pseudophakic dogs with implantation of two IOLs in piggyback (n=5) and (PL) pseudophakic dogs with implantation of a veterinary IOL (n = 5). The ultrasound was carried under the administration of a topic local anesthetic, with a multi frequency linear transducer of 10 MHz. Biometric eye measurements were also performed. The clinical alterations observed were IOL dislocation, retinal detachment, asteroid hyalosis, and vitreous degeneration. Ultrasound examination was an excellent diagnostic tool, as it was possible to confirm and classify these changes. The piggyback implant reduced the measurements between the ciliary body and the vitreous chamber obtained from the ocular biometry when compared to other usual procedures, with no difference between the axial length and the anterior chamber.